Possible relationship between respiratory diseases and urinary concentrations of polycyclic aromatic hydrocarbon metabolites - a pilot study - Gomersall, Veronika; Ciglová, Kateřina; Barošová, Hana; Hoňková, Kateřina; Solanský, Ivo; Pastorková, Anna; Šrám, Radim J; Schmuczerová, Jana; Pulkrabová, Jana (Journal of applied biomedicine, 2024)
This study investigates the potential relationship between exposure to polycyclic aromatic hydrocarbons (PAHs), specifically monohydroxylated metabolites (OH-PAHs), in urine, and the prevalence of respiratory diseases in 2-year-old children residing in two locations within the Czech Republic - České Budějovice (control location) and the historically contaminated mining district of Most. Despite current air quality and lifestyle similarities between the two cities, our research aims to uncover potential long-term health effects, building upon previous data indicating distinctive patterns in the Most population. A total of 248 urine samples were analysed for the presence of 11 OH-PAHs. Employing liquid-liquid extraction with ethyl acetate and clean-up through dispersive solid-phase extraction, instrumental analysis was conducted using ultra-high performance liquid chromatography coupled with tandem mass spectrometry. The incidence of respiratory diseases was assessed through questionnaires administered by paediatricians. The concentrations of OH-PAHs were elevated in urine samples from 2-year-olds in Most compared to those from České Budějovice. The incidence of respiratory diseases showed statistically significant higher levels of OH-PAHs in children from Most, together with a higher incidence of influenza. This association underlines the impact of environmental PAH exposure on children's respiratory health. It suggests that elevated urinary OH-PAH levels indicate an increased risk of developing respiratory diseases in the affected population. Further studies are needed to clarify the possible long-term health effects and to contribute to sound public health strategies.
Keywords: vystavení vlivu životního prostředí; Česká republika; Child, Preschool; lidé; Female; mužské pohlaví; Pilot Projects; předškolní dítě; Male; Environmental Exposure; Czech Republic; polycyklické aromatické uhlovodíky; nemoci dýchací soustavy; pilotní projekty; Respiratory Tract Diseases; Polycyclic Aromatic Hydrocarbons; ženské pohlaví; Humans